P25 and P37 proteins encoded by firespike leafroll-associated virus are viral suppressors of RNA silencing - Wang, Yaqin; Liu, Hui; Wang, Zhanqi; Guo, Yushuang; Hu, Tao; Zhou, Xueping (Frontiers in Microbiology, 2022)
Firespike leafroll-associated virus (FLRaV) is a major pathogen associated with firespike (Odontonema tubaeforme) leafroll disease. Phylogenetic analysis showed that FLRaV possesses typical traits of subgroup II members of ampeloviruses, but encodes two additional proteins, P25 and P37. Here, we determined the microfilament localization of P25 protein. Posttranscriptional gene silencing (PTGS) assay showed that both FLRaV P25 and P37 were able to suppress the local and systemic PTGS and FLRaV P25 was capable of suppressing the green fluorescent protein (GFP) gene silencing triggered by both sense RNA-induced PTGS (S-PTGS) and inverted repeat RNA-induced PTGS (IR-PTGS). In contrast, FLRaV P37 was only able to inhibit the GFP silencing triggered by the S-PTGS but not the IR-PTGS. In the transcriptional gene silencing (TGS) assay, only FLRaV P25 was found to be able to reverse established TGS-mediated silencing of GFP in 16-TGS plants. We also found that FLRaV P25 could aggravate the disease symptom and viral titer of potato virus X in N. benthamiana. These results suggest that FLRaV P25 and P37 may have crucial roles in overcoming host RNA silencing, which provides key insights into our understanding of the molecular mechanisms underlying FLRaV infection.